2010
DOI: 10.1348/026151009x416429
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dyadic interactions and coping with still‐face in healthy pre‐term and full‐term infants

Abstract: Pre-term birth has a significant impact on infants' social and emotional competence, however, little is known about regulatory processes in pre-term mother-infant dyads during normal or stressful interactions. The primary goals of this study were to investigate the differences in infant and caregiver interactive behaviour and dyadic coordination of clinically healthy pre-term compared to full-term infant-mother dyads and to examine pre-term infants' capacity for coping with stress using the face-to-face still-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 82 publications
8
77
3
5
Order By: Relevance
“…For instance, Leeb and Rejskind [64] found that female infants aged 3-4 months made more eye contact interaction with unfamiliar female adults. Montirosso et al [65] argued that infant eye contact may serve as a compensatory regulation strategy in preterm infants aged 6-9 months. It may be that female infants make more compensatory use of other-directed regulative strategy as opposed to self-comforting behaviors in the case of maternal disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Leeb and Rejskind [64] found that female infants aged 3-4 months made more eye contact interaction with unfamiliar female adults. Montirosso et al [65] argued that infant eye contact may serve as a compensatory regulation strategy in preterm infants aged 6-9 months. It may be that female infants make more compensatory use of other-directed regulative strategy as opposed to self-comforting behaviors in the case of maternal disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was greater for preterm infants, likely as a function of maternal modelling and contingency patterns, although with more negative emotions displayed by preterm infants. Another study which examined the infants' behaviours during face-to-face play and a still-face condition in a 6-to 9-month-old heterogeneous preterm group (<36 weeks GA), showed that the preterm infants spent a similar time in object/environment engagement and social monitoring as the full-term infants in the play condition; by contrast, lower self-regulatory abilities, with more distancing behaviours, were observed in the stressful still-face condition (Montirosso, Borgatti, Trojan, Zanini, & Tronick, 2010).…”
Section: Infants' Behaviours In Early Mother-preterm Infant Interactionmentioning
confidence: 99%
“…Firstly, infants cannot respond to parental expectations in the same way that full-term babies do. They tend to be less alert and responsive (Montirosso, Borgatti, Trojan, Zanini, & Tronick, 2010;Tallandini & Scalembra, 2006). Secondly, mothers typically feel unprepared due to the early birth, which challenges the attachment process (Borghini et al, 2006).…”
Section: Introductionmentioning
confidence: 99%